Effects of Wall Material on Medium-Chain Triglyceride (MCT) Oil Microcapsules Prepared by Spray Drying - Su Mon San; Montree Jaturanpinyo; Waree Limwikrant (Pharmaceutics, 2022)
A medium-chain triglyceride (MCT) oil microcapsule was prepared by spray drying. The effects of the wall-material parameters of wall-to-oil ratio (1:1 to 3:1) and type of wall material (gum arabic (GA), whey protein isolate (WPI), and octenyl succinic anhydride (OSA) starch) on the microcapsules were evaluated. The droplet size, size distribution, viscosity, zeta potential, and stability of the emulsions were measured. The spray-dried powder was characterized by its morphology, yield, encapsulation efficiency, and moisture content. The wall material influenced the characteristics of the emulsions and microcapsules. The formulation with a 2:1 wall-to-oil ratio and OSA starch/maltodextrin as the wall material resulted in a small droplet size (0.177 ± 0.002 µm) with high encapsulation efficiency (98.38 ± 0.01%). This formulation had good physical stability over three months under accelerated conditions. Thus, OSA starch/maltodextrin is an appropriate wall material for encapsulating MCT oil.